The Potential of In Vivo Imaging for Optimization of Molecular and Cellular Anti-cancer Immunotherapies - Fruhwirth, Gilbert O. (Mol Imaging Biol, 2018)
This review aims to emphasize the potential of in vivo imaging to optimize current and upcoming anti-cancer immunotherapies: spanning from preclinical to clinical applications. Immunotherapies are an emerging class of treatments for a variety of diseases. The agents include molecular and cellular therapeutics, which aim to treat the disease through re-education of the host immune system, often via complex mechanisms of action. In vivo imaging has the potential to contribute in several different ways: (1) as a drug development tool to improve our understanding of their complex mechanisms of action, (2) as a tool to predict efficacy, for example, to stratify patients into probable responders and likely non-responders, and (3) as a non-invasive treatment response biomarker to guide efficient immunotherapy use and to recognize early signs of potential loss of efficacy or resistance in patients. Areas where in vivo imaging is already successfully implemented in onco-immunology research will be discussed and domains where its use offers great potential will be highlighted. The focus of this article is on anti-cancer immunotherapy as it currently is the most advanced immunotherapy area. However, the described concepts can also be paralleled in other immune-mediated disorders and for conditions requiring immunotherapeutic intervention. Importantly, we introduce a new study group within the European Society of Molecular Imaging with the goal to facilitate and enhance immunotherapy development through the use of in vivo imaging.